2010
DOI: 10.1021/jp911043r
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Investigation of Decomposition of Nano Zn4O(C8H4O4)3 Metal−Organic Framework

Abstract: The systematic investigation of thermal decomposition of the metal-organic framework Zn 4 O(BDC) 4 (MOF-5) was carried out. It was found that the decomposition of MOF-5, which could take place at 400 °C or above, was due to the breaking of carboxylic bridges between benzene rings and Zn 4 O clusters. The decomposition produced CO 2 , benzene, and amorphous carbon besides crystal ZnO. Furthermore, the ZnO was covered by amorphous carbon, resulting in the C/ZnO nanoparticles of about 10 nm. The removal of ZnO fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(50 citation statements)
references
References 66 publications
3
47
0
Order By: Relevance
“…[29] Moreover, the breaking of the carboxylic bridges between Zn 4 O clusters and benzene rings is very important in the degradation of MOF-5 to produce C/ZnO. [30] The relative thermal stability of the isotypic M-BDCs observed in this study (Al-BDC > Cr-BDC > V-BDC) cannot be explained by the strength of the metal-oxygen bonds, because the average bond strength or bond dissociation energy follows the order of V À O (637) > Al À O (502) > Cr À O (461 kJ mol À1 ). [44] Moreover, the inertness or lability cannot be applied to explain the thermal stability.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
See 2 more Smart Citations
“…[29] Moreover, the breaking of the carboxylic bridges between Zn 4 O clusters and benzene rings is very important in the degradation of MOF-5 to produce C/ZnO. [30] The relative thermal stability of the isotypic M-BDCs observed in this study (Al-BDC > Cr-BDC > V-BDC) cannot be explained by the strength of the metal-oxygen bonds, because the average bond strength or bond dissociation energy follows the order of V À O (637) > Al À O (502) > Cr À O (461 kJ mol À1 ). [44] Moreover, the inertness or lability cannot be applied to explain the thermal stability.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…[29] MOF-5 decomposed into C/ZnO at high temperature. [30] By using TGA (thermogravimetric analysis) and TPMS (temperature-programmed mass spectrometry) methods, it has been found that the decomposition of MOF-5 occurs at 400 8C or above and is due to the breaking of carboxylic bridges between the Zn 4 O clusters and benzene rings. [30] MOF-177 decomposes in water in 12 h and the structure is also gradually changed from hexagonal to orthogonal, and finally to monoclinic phase in five weeks at ambient condition, showing the poor stability of MOF-177.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As seen from XRD patterns in Fig and correspondent to the diffraction peaks of ZnO [20,21], indicating that the carbonization at 500 and 700 °C resulted in the decomposition of framework of MOF-5 and the formation of ZnO@carbon. This is because the Zn-O subunits in MOF-5 can act as a ZnO source to assemble into ZnO particles during the thermal decomposition [21]. Increasing the carbonization temperature to 850 °C (Fig.…”
Section: Insert Figmentioning
confidence: 76%
“…Specially, during carbonization, conventional micropores gradually emerged, and highly dispersed Zn 2+ matrix embedded in the carbon matrix was reduced to Zn. The vaporization of Zn subsequently led to the creation of nanopaths [37][38][39][45][46][47]. Meanwhile, the core-shell nanostructures of HCSs-Zn-910 are retained after pyrolysis at 910°C, and the sphere sizes are ca.…”
Section: Structural Properties Of Microporous Hollow Carbon Spheresmentioning
confidence: 99%